Inexperienced preys know when to flee or to freeze in front of a threat - Hébert, Marie; Versace, Elisabetta; Vallortigara, Giorgio (Proceedings of the National Academy of Sciences - PNAS, 2019)
Using appropriate antipredatory responses is crucial for survival. While slowing down reduces the chances of being detected from distant predators, fleeing away is advantageous in front of an approaching predator. Whether appropriate responses depend on experience with moving objects is still an open question. To clarify whether adopting appropriate fleeing or freezing responses requires previous experience, we investigated responses of chicks naive to movement. When exposed to the moving cues mimicking an approaching predator (a rapidly expanding, looming stimulus), chicks displayed a fast escape response. In contrast, when presented with a distal threat (a small stimulus sweeping overhead) they decreased their speed, a maneuver useful to avoid detection. The fast expansion of the stimulus toward the subject, rather than its size per se or change in luminance, triggered the escape response. These results show that young animals, in the absence of previous experience, can use motion cues to select the appropriate responses to different threats. The adaptive needs of young preys are thus matched by spontaneous defensive mechanisms that do not require learning.